Für Johannes Gebhardt. - Gebhardt, Christa; Haarmann, Rainer (Salzau : Landeskulturzentrum, 1994)
Abraham, Kerstin ; Gebhardt, Christa ; Gebhardt, Johannes ; Simon-Weidner, Rolf ; Thieme, Ekkehard ; Vehring, Fritz ; Vehring, Vera
Für Johannes Gebhardt, Landeskulturzentrum Salzau, Salzau, 25. September 1994 bis 22. Januar 1995
boek